The Interplay Between Plasma Hormonal Concentrations, Physical Fitness, Workload and Mood State Changes to Periods of Congested Match Play in Professional Soccer Players - Saidi, Karim; Ben Abderrahman, Abderraouf; Boullosa, Daniel; Dupont, Grégory; Hackney, Anthony C.; Bideau, Benoit; Pavillon, Thomas; Granacher, Urs; Zouhal, Hassane (Frontiers in Physiology, 2020)
Background: The regular assessment of hormonal and mood state parameters in professional soccer are proposed as good indicators during periods of intense training and/or competition to avoid overtraining. Objective: The aim of this study was to analyze hormonal, psychological, workload and physical fitness parameters in elite soccer players in relation to changes in training and match exposure during a congested period of match play. Methods: Sixteen elite soccer players from a team playing in the first Tunisian soccer league were evaluated 3 times (T1, T2, and T3) over 12 weeks. The non-congested period of match play was from T1 to T2, when the players played 6 games over 6 weeks. The congested period was from T2 to T3, when the players played 10 games over 6 weeks. Physical performances and plasma Cortisol (C), Testosterone (T), and the T/C ratio were measured at T1, T2, and T3. Players had their mood dimensions (tension, depression, anger, vigor, fatigue, confusion, and a Total Mood Disturbance) assessed through the Profile of Mood State questionnaire (POMS). Training session rating of perceived exertion (sRPE) was also recorded on a daily basis in order to quantify internal training load, monotony and strain. Results: T and T/C were significantly lower in T3 when compared with T2 and T1 (p=0.03, ES3-2=0.14, ES3-1=0.56, T/C: p=0.017, ES3-2=0.04, ES3-1=0.61). Significant changes were observed over the study period for mood dimensions. Between T1-T2, significant relationships were observed between workload and changes in T (r=0.66, p=0.003), and T/C ratio (r=0.62, p=0.01). Between T2-T3, there was a significant relationship between Δ% of total mood disturbance and Δ% of Yo-Yo running test level 1 (r=-0.54; p=0.04), repeated sprint performance (r= 0.58, p=0.01), SJ (r=-0,55, p=0.01), T (r=0.53; p=0.03), and T/C (r=0.5; p=0.04). Conclusions: An intensive period of congested match play significantly compromised elite soccer players’ physical and mental fitness. These changes were related to psychological but not hormonal parameters; even though significant alterations were detected for selected measures. Mood monitoring could be a simple and useful tool to determine the degree of preparedness for match play during a congested period in professional soccer.